DIGITALIZATION OF RAMADAN DA'WAH: EFFECTIVE STRATEGIES FOR ISLAMIC EDUCATION IN THE TECHNOLOGICAL ERA - Fatmawati, Endang (Indonesian Journal of Studies on Humanities, Social Sciences and Education, 2025)
The rapid evolution of digital technology has significantly transformed Islamic education practices, particularly the delivery of Ramadan Da'wah, necessitating a scholarly exploration of effective digital strategies. Employing a systematic literature review approach, this study investigates contemporary methodologies utilized in digital platforms to optimize Islamic education during Ramadan. Scholarly articles indexed in reputable databases were critically analyzed to identify prevailing trends, digital tools, and strategic frameworks applied across diverse Islamic contexts. The findings highlight the extensive utilization of social media, mobile applications, and virtual platforms as dominant channels for disseminating Ramadan-related religious knowledge. Several strategies, including interactive multimedia content, personalized learning experiences, and collaborative online environments, emerged prominently as effective means of enhancing learner engagement and comprehension. Despite notable advancements, the literature underscores critical challenges, such as maintaining authentic religious teachings, mitigating misinformation risks, and ensuring inclusivity across varying demographic segments. Furthermore, successful implementation of digital Ramadan Da'wah requires educators' digital literacy enhancement, content moderation mechanisms, and robust community engagement. This study contributes a structured synthesis of digital strategies, providing theoretical insights and practical guidance for educational institutions aiming to leverage technology effectively during Ramadan. Future research directions should focus on empirical validation of identified strategies, analysis of learner experiences, and longitudinal assessments of educational outcomes.